An unusual case of transient cortical blindness with sagittal sinus thrombosis in a case of Henoch-Schonlein purpura - Samanta, S K; Mahapatra, N; Aich, B; Sarkar, N; Chatterjee, A (Nepalese Journal of Ophthalmology, 2012)
Introduction: Henoch-Schonlein purpura (HSP) is one of the most common causes of small vessel vasculitis in children, but sometimes may have an atypical presentation. Objective: To report an unusual case of transient cortical blindness in a patient with Henoch-Schonlein purpura. Case: A 3-year-old female child was brought with the complaint of diffuse abdominal pain and hematochezia, which was preceded by high grade fever and cough. Three days later she developed hematuria, hematemesis, melena and hemoptysis along with palpable purpura. Four days later she became irritable and developed a few episodes of generelized tonic clonic seizure, followed by cortical blindness. The CT scan of the brain showed bilateral nonenhancing occipital hypodensity. The magnetic resonance venography showed thrombosis in transverse and sigmoid sinus. She was treated with corticosteroids and her mental status and vision improved. Conclusion: The HSP can cause transient cortical blindness, and recovery is good if therapy is initiated at the appropriate time. DOI: http://dx.doi.org/10.3126/nepjoph.v4i2.6556 Nepal J Ophthalmol 2012; 4 (2): 333-335